2015
DOI: 10.1093/cid/civ859
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hepatitis B and Hepatitis C Infections and Benefits of Programs for Hepatitis Prevention in Northeastern China: A Cross-Sectional Study

Abstract: ChiCTR-ECS-13004009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 20 publications
8
56
0
Order By: Relevance
“…China is among the countries with high endemicity with HBsAg-positivity rates varying by geography and subpopulation [1618]. However, the results of HCV infection prevalence have been variegated in previous studies [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…China is among the countries with high endemicity with HBsAg-positivity rates varying by geography and subpopulation [1618]. However, the results of HCV infection prevalence have been variegated in previous studies [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the national HBV vaccination campaign in China, HBV remains endemic, with 7% of the total Chinese population identified as afflicted with CHB[21,22]. Meanwhile, recent epidemiological study in China has indicated a past HEV infection rate of 20%-40% (anti-HEV IgG positivity) and an additional 1% of new infections annually[23-25].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from China showed that HBV prevalence in men in rural China has changed from highly endemic into intermediate endemic in the past two decades, but the absolute number of HBV-infected men and the susceptible population is still large 2 . Another recent study from China also showed that the hepatitis B surface antigen (HBsAg) positive rate was 6.1% 3 . Chronic hepatitis B (CHB) can lead to a progressive accumulation of liver fibrosis which progressively evolves to cirrhosis, hepatocellular carcinoma (HCC), liver failure, and death 4 .…”
Section: Introductionmentioning
confidence: 99%